Technology Entrepreneurship Project (ENT 600) : Under Armour / Mohamad Ismail Abdul Mutalib - Abdul Mutalib, Mohamad Ismail (2021)
In this pandemic, there’s a lot of changes in scheme of work. But this not a distracted for us to learn the theories about ENT 600. This case study is part of assignment on purpose to do research about company and their SWOT analysis of product. So, we choose Under Armour as our company to do this case study. As we know that Under Armour is one of the company that provide sports goods. Because of this project, I get chances to know deeply about this company such as their objective, mission, vision and many more. In this project, I need to choose one product and do SWOT analysis on that product. So, I choose their sport shoes which name” Under Armour Charged Assert 8”. Then I will identify the weakness and need overcome with my best solution. Through this case study, I will describe in detail about the problem and solution to overcome the product’s problem.